Watershed hydrological modelling in data scarce regions; integrating ecohydrology and regionalization for the southern Caspian Sea basin, Iran. Issue 4 (April 2021) - Sheikh Goodarzi, Mehdi; Jabbarian Amiri, Bahman; Azarnivand, Hossein; Waltner, István
Abstract: The aim of this study is to evaluate an alternative approach to indicate how hydrological processes behave in a given watershed, and to test whether this approach can replace traditional calibration, particularly under data deficient conditions. Therefore, a regional calibration method (RC) was adapted to characterize "parameter-based hydrologic processes" as a function of watershed ecologic attributes. The methodological process included (1) temporal phase, (2) correlation analysis and (3) spatial phase. The defined methodology was carried out on a 4160 km 2 area containing 21 watersheds laying in the southern coastal line of the Caspian Sea, Iran. By implementing the RC, regional models were specified corresponding to each hydrological process defined in the Tank model. Testing the reliability of the transferring process of hydrological parameters was conducted using multi-level accuracy comparison (MAC) benefiting from descriptive statistics, scatter-plots and T-test. Both temporal and spatial phases have shown acceptable outputs backed by their ecologic significance, but as an alternative approach to traditional calibration, the standalone RC still needs development to achieve a more robust basis covering all the parameters of the hydrologic model. According to the post-processor MAC, the transferability of six out of twelve regional models ( height of lower outlet at the first tank, intermediate flow, deep-percolation, infiltration, surface flow, height of outlet at the second tank ) was accepted with respect to the given tests. As such, our method outperformed the number of transferable parameters by an outstanding regional model predicting the surface flow in comparison with similar studies. Although the RC could not achieve total perfection, nevertheless it could still help users by providing more information about the contribution of ecologic variables in the prediction of the hydrological processes of a certain watershed. Abstract : Tank model, Rainfall-runoff relationship, Ecohydrological modelling, Regionalization approach, Caspian Sea basin, Donor and recipient watersheds.